Penerapan Ijarah Muntahiya Bit Tamlik pada Perusahaan Leasing dalam Perspektif Fikih Muamalah: Studi Kasus PT. Adira Finance - Hendra, Hendra; Putri, Rafika Chudriana; Sudiarti, Sri; Marliyah, Marliyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Currently, human needs are increasingly complicated, especially for vehicles as a means of support in every activity. Therefore, the role of Islamic financial institutions in this case is needed as a facilitator for people who are constrained by capital. Islamic financial institutions have a financing agreement "Ijarah Al Muntakiya bit Tamlik" (financial leasing with purchase)/IMBT as a solution to this problem. IMBT is a combination of leasing (ijarah) and buying and selling at the end of the lease contract. Purchase of vehicles on credit in leasing can be used as a community solution option. however, community literacy regarding leasing is still limited, especially in the fiqh muamalah approach. Method This research is a qualitative descriptive study in which the researcher describes the results that have been studied. Application of Ijarah Muntakiya Bittamlik (IMBT) at PT. Adira Finance is almost in accordance with the study of muamalah fiqh, except that in handling bad loans it uses a forced pick-up system on the main road as a warning to customers who are in arrears. If it is related to theory, this should have been avoided. But on the other hand, if at the end of the financing period or the consumer contract has paid off its obligations, the leasing party will provide BPKB as proof of transfer of ownership. Keywords: Ijarah Al Muntakiya bit Tamlik (IMBT), Leasing, PT. Adira Finance